(3QSGdI aj cdeI (B((3gPg(B)s - (3chRj Hjhc RGOg , EHQGgje Hf eMeO GdbjUQj, GHf GdGYjf,J (B1253 (3g` s
(3ChdgG (B:s
(3hHYO GYde Gf cdeI gPg ehVhY HGdhVY GdfhYi ddETGQI Edi GdeTGQ Edjg GdMGVQ GdeMShS jMS GdHUQ ETGQI MSjI s
(3BNQgG (B:s
(3Gf GdJYjfi ZjQ eYJHQ ai eaghe GSe GdLfS ,eYJHQ ai eaghe Yde GdLfS aXgQ GdaQb Hjf GdKdGK s
(3Vef eLehY , JQJjHgG (B: (3ef U (B235 - (3U(B237s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B90 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B608) s
Keywords: (3GdeYGQa GdYGeIs